Strategi Prodi Bisnis Dan Manajemen Dalam Menghasilkan Mahasiswa Sebagai Calon Wirausahawan - Lalita Vistari Satyananda (Jurnal Ilmiah Kampus: Sati Sampajanna, 2020)
2020 is the year of the pandemic COVID -19 which is concerned for the world. The world is experiencing shocks and the risk of increasing uncertainty and affecting various sectors, like the health, social and economic sectors. In the economic sector, economic activity has decreased. Several companies have laid off their employees because their businesses could not survive, decreased business productivity, which resulted in reduced public consumption and reduced economic growth. In a situation like this, humans are required to be able to adapt to existing conditions, by innovating to create new business fields or trying to become entrepreneurs to encourage economic growth. The economic activity amid the pandemic's challenges has been initiated by the government in order to the Indonesian economy will revive, including universities in Jakarta, Tangerang, and Bekasi are trying to create new entrepreneurs in the economic sector.The purpose of this research is to describe the strategy of universities in creating students as entrepreneurs amid the COVID-19 pandemic. The research subjects were the program managers, and the entrepreneurs’ lecturers. The research method used is descriptive qualitative using Miles and Huberman data analysis. The method used in this research was carried out through data collection, data reduction, data presentation, and conclusions.Based on the results of the research, it can be concluded that universities prepared students very well in terms of curriculum, teaching, entrepreneurial activities, and soft skills that students must have before graduating from tertiary education, such as students are required to make their own entrepreneurship while being students.